Motor Innervation of the Corrugator Supercilii Muscle in Relation to Orbital Landmarks: Guidelines for Surgical Denervation. Issue 5 (July 2016) - Lans, Jonathan; Schellekens, Pascal P.A.; de Ru, Jacob A.; Bleys, Ronald L.A.W.
Abstract : Abstract: Precise knowledge of the nerve supply of the corrugator supercilii muscle (CSM) is a prerequisite for performing a selective denervation of the CSM. The authors' goal was to determine the course and variability of the motor nerves of the CSM in relation to fixed orbital landmarks. The facial nerve branches toward the CSM were identified during microscopic dissection of 9 Caucasian formaldehyde-fixed cadaver half-heads. The distances between the branches and defined landmarks were measured. All branches to the transverse head of the CSM ran between 15 and 32 mm superior to the lateral orbital margin. Medially the CSM was supplied by a superficial zygomatic, buccal, or bucco-zygomatic branch, which was much smaller than the temporal branches. This branch ran 4 to 7 mm medial to the medial canthus. This anatomical knowledge can be applied for surgical denervation of the corrugator supercilii muscle. The authors suggest a surgical procedure for corrugator denervation through a blepharoplasty incision.